Characteristics of Eco-Friendly and Sustainable Plywood Adhesive derived from Low-Quality Cat’s Eye Damar Resin - Mia Putri Utami; Muhammad Adly Rahandi Lubis; Sandi Asmara; Samsul Bakri; Sri Hidayati; Wahyu Hidayat (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Wood panel products mainly use formaldehyde-based adhesives that release free formaldehyde and potentially cause health problems. This study aimed to develop a free-formaldehyde adhesive from cat’s eye damar (CED) resin as an alternative adhesive for plywood production. The low-quality CED resin was used to increase the added value of the resin. The adhesive formulation consists of a ratio of 30:70 (CED:benzene) dissolved for 15 minutes at 45°C. The plywood was manufactured using glue spread rates of 200, 250, and 300 g/m2 with an addition of 10% tapioca flour and hot pressed using a pressure of 2.45 MPa at 120°C for 6 minutes. The CED-based adhesive produced has a solid content of 28.76%, a pH value of 5.93, a gel time value of 70.05 minutes, and a viscosity value of 4.02 mPa.s. Fourier-transform infrared spectroscopy analysis stretching of the C-H group, indicating an alkane compound. Plywood’s physical and mechanical properties bonded with CED-based adhesive increased with higher glue spread application. Utilizing a glue spread of 300 g/m2 could produce plywood with comparable physical and mechanical properties to the urea-formaldehyde-bonded plywood. Keywords: cat’s eye damar, dynamic mechanical analysis, formaldehyde-free adhesive, plywood, Shorea javanica